PENGARUH MEDIA PEMBELAJARAN BERBASIS METODE MONTESSORI TERHADAP KEMAMPUAN MEMBACA DAN MENULIS SISWA KELAS I UPT SPF MINASA UPA KOTA MAKASSAR - Habib Agung Izzulhaq; Abd. Rahman Rahim; Ummu Khaltsum (Nusantara Hasana Journal, 2022)
The main problem in this study is how the influence of the use of learning media based on the Montessori method on the ability to read and write at the beginning of grade 1 at UPT SPF SDN Minasa Upa. This study aims to determine the effect of the use of learning media based on the Montessori method on reading ability and the beginning of class I UPT SPF SDN Minasa Upa. The results of the Hypothesis Test show the value of df = 10 and the value of 0.05/2 = 0.025. We use this value as a basic reference in finding the t table in the t table. Because t count tta table ( t count = 5,422 t table = 2,22814, thus H0 is rejected and H1 is accepted. It can be said that the use of learning media based on the Montessori method affects the reading and writing ability of grade I students at UPT SPF SD Negeri Minasa Upa. Results Based on the research and discussion, it can be concluded that the use of learning media based on the Montessori method in learning affects the ability to read and write at the beginning of class I at UPT SPF SD Negeri Minasa Upa Makassar City. This can be proven from the average score of student learning at the time of the pretest was 79.36 in the medium category and the average score at the posttest was 84.27 in the high category.